Deconstructing intercontinental invasion pathway hypotheses of the Mediterranean fruit fly (Ceratitis capitata) using a Bayesian inference approach: are port interceptions and quarantine protocols successfully preventing new invasions?. Issue 7 (10th April 2015) - Karsten, Minette; Jansen van Vuuren, Bettine; Addison, Pia; Terblanche, John S.; Leung, Brian
Abstract Aim Knowledge of how effective interceptions and quarantine measures are in preventing new biological invasions is of paramount importance for maintaining ecosystem function in a rapidly changing world. Here, we determine current macrogeographic population structure and routes of invasion of the Mediterranean fruit fly (Ceratitis capitata) using genetic approaches and reconstruct and test invasion pathway hypotheses in a Bayesian framework. Location Africa, Australia, Greece, Guatemala and Madeira. Methods We sampled 323 C. capitata individuals from 14 locations world‐wide and genotyped all individuals for 11 polymorphic microsatellite markers. We calculated measures of genetic diversity and determined population structure. Moreover, we reconstructed and tested eighteen invasion pathway scenarios in a Bayesian framework using ABC modelling. Results We show a decrease in genetic diversity outside the native range (Africa) into the introduced range (Australia, Greece, Guatemala and Madeira). The most likely invasion pathway scenario closely matched the historical records, with an initial colonization of Europe from Africa and a secondary colonization of Australia from Europe. Moreover, we show an introduction from Greece to the Americas and, finally, a back introduction into South Africa from Europe. Main conclusions Given the lack of new introductions into colonized (non‐African) locations despite increasing trade, and apart from the initial invasion and establishment of the species outside of Africa, we conclude that quarantine and interception measures have been largely successful to date.